Causal association between hyperthyroidism and risk of gastroesophageal reflux or esophageal cancer: a bidirectional Mendelian randomization investigation - Zhu, Xingyu; Li, Ming; Gan, Hanghang; Guo, Yingqiang (Frontiers in Endocrinology, 2024)
Emerging observational studies indicated an association between hyperthyroidism and gastrointestinal disorders. However, it remains unclear whether this association is causal, particularly in the case of gastroesophageal reflux (GERD) and esophageal cancer.To assess the potential causal relationship between hyperthyroidism and GERD or esophageal cancer, we conducted a bidirectional 2-sample Mendelian randomization study. Independent genetic instruments for hyperthyroidism from the UK Biobank (N case=3,545 and N control=459,388) and public genome-wide association study (GWAS) dataset (N case=3,731 and N control=480,867) were used to investigate the association with esophageal cancer in the UK Biobank study (N case=740 and N control=372,016) and GERD in the public GWAS database (N case=20,381 and N control=464,217). Four different approaches (inverse variance weighted (IVW), weighted mode, MR-Egger, and weighted median regression) were used to ensure that our results more reliable.Additional sensitivity analyses were also performed to validate our results.When hyperthyroidism was considered as the exposure factor, it appeared to act as a protective factor for GERD (ORIVW = 0.88, 95% CI, 0.79-0.99, P = 0.039), while as a risk factor for esophageal cancer (ORIVW = 1.03, 95% CI, 1.01-1.06, P = 0.003).However, there is no evidence supporting a reverse causal relationship between genetic susceptibility to hyperthyroidism and GERD or esophageal cancer.Our findings provided genetic evidence supporting bidirectional causal relationships between hyperthyroidism and GERD or esophageal cancer. These results substantiate certain discoveries from previous observational studies on a causal level and provide insight into relevant genetic susceptibility factors.